Computer-Designed Splints for Surgical Transfer of 3D Orthognathic Planning - Zinser, Max; Zoeller, Joachim (Facial Plastic Surgery, 2015)
Advances in computers and imaging have permitted the adoption of three-dimensional (3D) planning protocols in orthognathic surgery, which may allow a paradigm shift when the computer-assisted planning can be transferred properly. The purpose of this investigation was to introduce an innovative clinical protocol using computer-aided designed and computer-aided manufactured (CAD/CAM) surgical splints for surgical transfer of 3D orthognathic planning compared with the classic technique using arbitrary occlusal splints. The clinical protocols consisted of computed tomography (CT) or cone-beam CT (CBCT) maxillofacial imaging, bone segmentation, 3D diagnosis, computer-assisted surgical treatment planning, and CAD/CAM surgical splints (group A) and manufacture of arbitrary occlusal splints (group B) for intraoperative surgical planning transfer. The observed patients underwent bimaxillary osteotomies and, if necessary, an additional genioplasty. Both techniques were evaluated by applying 13 hard tissue parameters to compare the 3D orthognathic planning (T0) with the postoperative result (T1) using 3D cephalometry. The CAD/CAM splints showed significant better precision for the maxilla (ΔT < 0.23 mm) and mandible (ΔT < 0.33 mm) compared with a maxillary deviation of 1.3 mm and a mandibular deviation of 1.8 mm when using the arbitrary splints. Computer-assisted diagnosis and preoperative surgical planning provide clinicians with valuable tools and allow 3D imagination. CAD/CAM splints provide a reliable, innovative, and precise approach for the transfer of 3D orthognathic planning, which is more precise compared with the conventional arbitrary occlusal splints.
Keywords: computer-assisted orthognathic surgery; virtual planning; facial profile; rapid prototyping; CAD/CAM technology